2017
DOI: 10.1159/000480354
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum Phosphorus Levels Were Associated with Metabolic Syndrome in Men But Not in Women: A Cross-Sectional Study among the Japanese Population

Abstract: unexpectedly positively correlated with SP levels in women. Reduced SP levels were associated with MetS in men but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…To date, no study has been conducted to assess the association between serum phosphate concentration and HOMA-IR. The observed inverse association of serum phosphate concentration with FPG is in agreement with the findings of previous studies [ 14 , 15 , 16 ]. In a large Japanese study conducted among 16,041 individuals undergoing routine health checkups at the Iida Municipal Hospital [ 15 ], serum phosphate concentration was significantly and inversely associated with FPG.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…To date, no study has been conducted to assess the association between serum phosphate concentration and HOMA-IR. The observed inverse association of serum phosphate concentration with FPG is in agreement with the findings of previous studies [ 14 , 15 , 16 ]. In a large Japanese study conducted among 16,041 individuals undergoing routine health checkups at the Iida Municipal Hospital [ 15 ], serum phosphate concentration was significantly and inversely associated with FPG.…”
Section: Discussionsupporting
confidence: 93%
“…To date, few studies have investigated the association of serum calcium [ 7 , 11 , 12 , 13 , 14 ] and phosphate [ 7 , 14 , 15 , 16 ] concentrations with glucose metabolism markers, such as IR, fasting plasma glucose (FPG), or glycated hemoglobin (HbA1c). Among them, some [ 11 , 12 , 13 , 14 ], although not all [ 7 ], studies have reported that elevated calcium concentration is associated with increased FPG [ 11 , 12 , 14 ], IR [ 11 , 12 , 13 ], and HbA1c [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies that PTH level was higher in T2DM patients than the control but it was not significantly. PTH could increase intracellular calcium in skeletal muscle and adipocytes, which would consequently suppress glucose uptake by those tissues and induce IR 42 . Differences in the prevalence of vitamin D deficiency in males and females may contribute to the different degrees of association between PTH and vitamin D 44 .…”
Section: Effect Of Gender On Calcium Regulating Hormones In T2dm Patimentioning
confidence: 99%